A framework for searching encrypted databases - Alves, Pedro Geraldo M. R.; Aranha, Diego F. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2016: Anais do XVI Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2016.19304, 2016)
Cloud computing is a ubiquitous paradigm. It has been responsible for a fundamental change in the way distributed computing is performed. The possibility to outsource the installation, maintenance and scalability of servers, added to competitive prices, makes this platform highly attractive to the industry. Despite this, privacy guarantees are still insufficient for data processed in the cloud, since the data owner has no real control over the processing hardware. This work proposes a framework for database encryption that preserves data secrecy on an untrusted environment and retains searching and updating capabilities. It employs order-revealing encryption to provide selection with time complexity in Θ(log n), and homomorphic encryption to enable computation over ciphertexts. When compared to the current state of the art, our approach provides higher security and flexibility. A proof-of-concept implementation on top of MongoDB is offered and presents an 11-factor overhead for a selection query over an encrypted database.